Diversity and Abundance of the Species of Arboreal Mammals in a Tropical Rainforest in Southeast Mexico - J. Vladimir Rojas‐Sánchez; Rosamond Ione Coates; Víctor Sánchez‐Cordero; Mario C. Lavariega; José J. Flores‐Martínez (Ecology and Evolution)
ABSTRACT Habitat loss threatens biodiversity worldwide being particularly detrimental in tropical rainforests where a cumulative deforestation expands for decades. Tropical rainforests harbor a rich mammal diversity with a wide range of species using different habitats, ranging from forest‐dwelling to arboreal species. Recent techniques such as camera trapping have proven to be useful to study the ecology of arboreal mammals. Here, we assessed the overall community structure of arboreal mammals in a protected area by analyzing the patterns of diversity and abundance and their spatial and seasonal variations. A total of 21 camera‐trapping stations were set in clusters in three zones. Spatial and seasonal alpha‐diversity and community evenness patterns were estimated using Hill's numbers, and Sørensen's dissimilarities were used as a proxy to estimate beta‐diversity. A relative abundance index was calculated for each species, at each site and season. To estimate the influence of spatial and tree morphology on arboreal use by mammals, a Principal Component Analysis was performed. We observed a high species richness (14 species) of arboreal mammals. Species richness remained similar between sites, although shifts in abundances and a decreasing gradient in community evenness related to the distance of camera trap station located in each site were noted. We observed a high‐ and low‐diversity dissimilarity between camera trap stations and between zones, respectively. Seasonality showed no significant effect over abundance, alpha, and beta diversities. This protected area holds the natural habitat conditions to ensure the persistence of this rich arboreal mammal community.